2021
DOI: 10.1002/smll.202003937
|View full text |Cite
|
Sign up to set email alerts
|

Limbal Stem Cells on Bacterial Nanocellulose Carriers for Ocular Surface Regeneration

Abstract: Limbal stem cells (LSCs) are already used in cell‐based treatments for ocular surface disorders. Clinical translation of LSCs‐based therapies critically depends on the successful delivery, survival, and retention of these therapeutic cells to the desired region. Such a major bottleneck could be overcome by using an appropriate carrier to provide anchoring sites and structural support to LSC culture and transplantation. Bacterial nanocellulose (BNC) is an appealing, yet unexplored, candidate for this applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…[ 62 ] Amorphous materials and good thermal insulators tend to be abundant in biologically derived materials; to enhance their thermal conductivity, self‐assembled biomaterials with a higher degree of crystallinity and higher anisotropy are desirable. [ 63 ] BNC has already shown promising results as a scaffold in regenerative medicine, [ 17 , 18 , 19 , 64 ] we studied the influence of the geometrical order on the thermal conductivity of BNC fibers. In particular, we show that it is possible to enhance the thermal conductivity by directional alignment of the fibers, i.e., in the direction parallel to the alignment direction.…”
Section: Resultsmentioning
confidence: 99%
“…[ 62 ] Amorphous materials and good thermal insulators tend to be abundant in biologically derived materials; to enhance their thermal conductivity, self‐assembled biomaterials with a higher degree of crystallinity and higher anisotropy are desirable. [ 63 ] BNC has already shown promising results as a scaffold in regenerative medicine, [ 17 , 18 , 19 , 64 ] we studied the influence of the geometrical order on the thermal conductivity of BNC fibers. In particular, we show that it is possible to enhance the thermal conductivity by directional alignment of the fibers, i.e., in the direction parallel to the alignment direction.…”
Section: Resultsmentioning
confidence: 99%
“…Its potential application for invasion testing would require the functionalization of BNC with the extracellular matrix components through chemical or genetic modifications [ 40 , 41 ]. However, the surface functionalization of BNC affects the cells by altering their attachment and survival, which may influence the obtained results when such scaffolds are used for invasion testing [ 18 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Anton-Sales et al [ 86 ] found that, compared with the human amniotic membrane, the BNC shows a slightly longer stability and higher mechanical resistance to sutures in vitro under physiological conditions, or ex vivo under simulated physiological conditions. Building on these findings, they attempt to utilize BNC as the carrier for human embryonic stem cell-derived LSC (hESC-LSC) to validate the transplant potential of these cells in a follow-up investigation [ 87 ]. The results showed that self-renewal and stemness characteristics of hESC-LSC can be maintained up to 21 days on the BNC substrates.…”
Section: The Classification Of Bioinspired Nanostructured Systemsmentioning
confidence: 99%